Analisis Perputaran Piutang Vs Perputaran Hutang Lancar Dalam Rangka Meningkatkan Tingkat Likuiditas PT Unilever Indonesia Dan PT Mayora Indah - Hidayat, Lukman; Susanto, David (Jurnal Ilmiah Ranggagading (JIR), 2011)
Payable account analysis is short term liabilities to be paid in a period of a year including loans, short term loans and short term obligations such as taxes in progress and interest. Liquidity ratio describes company in complying with itsshort term obligations when they are mature. Its linkage with current debt ratio is the sooner the current debts are paid the more exact the impact of liquidity ratio level of the company to pay its payable debts. The purpose of this study is to look for information and to find out the truth of how far payable account turnover is influenced by the liquidity ratio. The evaluation result of this study is that a good working capital turnover will result in profitability, so the company has power to run its business properly.